2014
DOI: 10.3846/13923730.2013.802710
|View full text |Cite
|
Sign up to set email alerts
|

Positive Interaction of Industrial and Recycled Steel Fibres in Fibre Reinforced Concrete

Abstract: Abstract. In line with current "green" transport initiatives, Croatia plans to build over the next investment period a high speed railway line which will connect central Croatia and its capital with coastal regions of the country. According to design documents, the track system will be built using ballastless concrete solutions. In the scope of the project "Concrete track system -ECOTRACK", researchers from the University of Zagreb -Faculty of Civil Engineering analysed a new material, i.e. the rubberized hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 25 publications
2
38
0
1
Order By: Relevance
“…For a low dosage (<0.5% by volume) of steel fibers added in concrete, many studies have suggested that fiber addition has an insignificant effect on the compressive strength of concrete. Existing design guidelines (e.g., RILEM TC 162‐TDF and Model Code 2010) mainly focus on the tensile properties of SFRC, as in most applications (e.g., pavements and tunnel linings), the material is subjected to bending.…”
Section: Introductionmentioning
confidence: 99%
“…For a low dosage (<0.5% by volume) of steel fibers added in concrete, many studies have suggested that fiber addition has an insignificant effect on the compressive strength of concrete. Existing design guidelines (e.g., RILEM TC 162‐TDF and Model Code 2010) mainly focus on the tensile properties of SFRC, as in most applications (e.g., pavements and tunnel linings), the material is subjected to bending.…”
Section: Introductionmentioning
confidence: 99%
“…Research presented hereafter is part of a large FP7 project, Anagennisi [16,17], where the aim of the project is to identify suitable applications for RTPF in concrete and to put an end to the current practice of landfilling this material. Based on the limited literature data [18][19][20][21], RTPF do not induce negative effects on concrete mechanical properties and could potentially have beneficial effect on controlling cracking of concrete due to different early age deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Opsežno istraživanje pokazalo je da se svaki od proizvoda dobivenih reciklažom otpadnih guma (slika 8) može koristiti u betonu, te istovremeno poboljšati određena svojstva betona [20][21][22][23]. U suradnji sa industrijskim partnerima, razvijena su dva inovativna proizvoda, a u sklopu novog EU projekta planira se razviti još inovativnih proizvoda, iskorištavaju pojedina svojstva reciklata automobilskih guma kako bi se pripremili specifični betonski proizvodi.…”
Section: Slika 8 Guma čElična I Tekstilna Vlakna Dobivena Reciklažounclassified
“…The extensive research performed on University of Zagreb Faculty of Civil Engineering implied positive effects when those are incorporated in concrete, either as replacement for raw materials or as a certain chemical admixtures [20][21][22][23]. In cooperation with industrial partners, researchers from the University of Zagreb, Faculty of Civil Engineering have developed two different construction products, which are utilising particular property of recycled tyres, to create solutions with added values on the market.…”
Section: Slika 8 Guma čElična I Tekstilna Vlakna Dobivena Reciklažomentioning
confidence: 99%